Influence of the strap rewind height during a conical pulley exercise - Sabido, R.; Hernández-Davó, J. L.; García-Valverde, A.; Marco, P.; Asencio, P. (Journal of Human Kinetics, 2020)
The use of flywheel devices has increased in popularity within resistance training programs. However, little is known about modifiable variables which may affect power output responses, as the rope length and the height level used in a conical pulley device. The aim of this study was to assess the influence of using three different rope lengths (1.5, 2.5 and 3.5 meters) and four different height levels (L1, L2, L3 and L4) on concentric peak power (PPconc), eccentric peak power (PPecc) and eccentric overload (eccentric/concentric PP ratio; EO) during conical pulley exercises (i.e. seated and stand-up row). A total of 29 recreationally trained subjects (25.3±7.1 years; 1.74±0.06 m; 72.5±8.3 kg) took part in the study. Testing sessions consisted of 1 set of 10 repetitions under each condition; experiment 1: seated row exercise using the three different rope lengths; experiment 2: stand-up row exercise using four different height levels of the conical pulley. Results from experiment 1 did not show differences between rope lengths, although a trend for greater PPecc (ES=0.36-0.38) and EO (ES=0.40-0.41) was found when using longer rope lengths (2.5 and 3.5). Experiment 2 showed significant increases in both PPconc and PPecc as the height level used was closer to the cone base (L4). In contrast, EO values were significantly greater when using upper height levels (L1). These results suggest that the height level used during conical pulley exercises highly influences power output responses. Therefore, this variable should be carefully managed depending on the training goal (e.g. power vs hypertrophy).